Values and Preferences of Physicians and Patients With Nonvalvular Atrial Fibrillation Who Receive Oral Anticoagulation Therapy for Stroke Prevention - Andrade, Jason G.; Krahn, Andrew D.; Skanes, Allan C.; Purdham, Daniel; Ciaccia, Antonio; Connors, Sean (Canadian journal of cardiology, 2016)
Real-world data on patients' and physicians' values related to the use of oral anticoagulant (OAC) therapy for stroke prevention in patients with nonvalvular atrial fibrillation are currently lacking. We sought to assess the values, preferences, and experience of patients who receive OAC therapy, and of physicians who prescribe OAC therapy. A national survey of randomly selected patients (n = 266) and physicians (n = 178) was conducted between May and September 2014. Each was asked to evaluate the importance of individual OAC attributes and identify which of 2 medication profiles they would prefer (individual attributes were progressively modified to determine which were the most valued and/or influenced treatment choice). Medication adherence and prescription practice was also assessed. The preferences of patients and physicians regarding OAC therapy differed but largely focused on characteristics related to safety and, to a lesser extent, efficacy. When based solely on the basis of the attribute profile (blinded to the specific agent), physicians were more likely to select apixaban (61%), whereas patients showed no significant preference among apixaban, rivaroxaban, and warfarin. Despite this, 49% of physicians spontaneously stated rivaroxaban as their preferred agent (vs 25% apixaban). Patients prescribed and taking once daily medications (rivaroxaban or warfarin) showed better compliance with their OAC therapy (approximately 30% of twice daily medications being taken once daily, with significantly more missed doses compared with once daily medications). Real-world prescriptions do not reflect reported values, which suggests that other factors influence patient-physician decision-making around OAC therapy. Data on self-reported adherence to OAC therapy and discordance in the use of OACs from prescribed regimens are concerning and warrant further investigation. Il y a actuellement pénurie de données réelles, tant du côté des médecins que des patients, en ce qui a trait au traitement préventif de l’accident vasculaire cérébral (AVC) par un anticoagulant oral chez les patients atteints de fibrillation auriculaire non valvulaire. C’est pourquoi nous avons entrepris de sonder les patients et les médecins au sujet de leurs préférences et de leurs expériences à l’égard de la prise ou de la prescription du médicament, respectivement. Entre mai et septembre 2014, un sondage national a été mené auprès de patients (n = 266) et de médecins (n = 178) sélectionnés au hasard. On a demandé aux participants d’évaluer l’importance de diverses caractéristiques de ce type d’agent et de choisir les deux profils de médicament qu’ils préféraient (les caractéristiques étaient modifiées de manière progressive en vue de déterminer lesquelles étaient les plus prisées et/ou influaient sur le choix du traitement). Le sondage a aussi permis de vérifier l’observance du traitement et les habitudes de prescription du médicament. Les préférences différaient entre les patients et les médecins, mais dans les deux cas elles étaient essentiellement axées sur des caractéristiques liées à l’innocuité et, dans une moindre mesure, à l’efficacité. Lorsqu’ils se basaient uniquement sur le profil du médicament (le nom de l’agent n’était pas dévoilé), les médecins ont choisi le plus souvent l’apixaban (dans 61 % des cas), tandis que les patients n’ont pas semblé avoir de préférence significative pour un agent ou pour un autre (apixaban, rivaroxaban et warfarine). En dépit de cela, 49 % des médecins ont spontanément cité le rivaroxaban à titre de médicament de choix (vs l’apixaban dans 25 % des cas). L’observance du traitement était supérieure chez les patients à qui on avait prescrit un médicament à prise uniquotidienne (rivaroxaban ou warfarine) puisque dans environ 30 % des cas, les médicaments à prise biquotidienne n’étaient pris qu’une seule fois par jour, entraînant ainsi un nombre significativement plus élevé de doses manquées par rapport aux médicaments à prise uniquotidienne. Les ordonnances rédigées en pratique clinique ne reflètent pas les données recueillies lors du sondage, ce qui laisse penser que d’autres facteurs influent sur la prise de décision des médecins et des patients en matière d’anticoagulants oraux. De plus, les données relatives à l’observance du traitement et à l’écart entre la prise réelle et les schémas posologiques des médicaments sont inquiétantes et justifient la tenue d’études additionnelles.